Role of Somatostatin Receptor in Pancreatic Neuroendocrine Tumor Development, Diagnosis, and Therapy - Hu, Yuheng; Ye, Zeng; Wang, Fei; Qin, Yi; Xu, Xiaowu; Yu, Xianjun; Ji, Shunrong (Frontiers in Endocrinology, 2021)
Pancreatic neuroendocrine tumors (pNETs) are rare diseases that are part of the diverse family of neuroendocrine neoplasms (NENs). Somatostatin receptors (SSTRs), which are widely expressed in NENs, especially in pNETs, are G-protein coupled receptors that can be activated by somatostatins or its synthetic analogs. Therefore, SSTRs have been widely researched as a marker and target for diagnosing and treating in pNETs. An accumulation of studies has demonstrated the vital clinical significance of SSTRs in pNETs. A summary of the progress shown in these studies is urgently needed as it may contribute to novel and superior management of patients with pNETs, in addition to indicating the direction of future research. In this review, relevant literature has been appraised to summarize the most up to date collective knowledge and comprehension of the clinical significance of SSTRs in pNETs. Overall, SSTRs have great value in the diagnosis, treatment, and prognostic prediction of pNETs, however further research is necessary.